The Political Significance of Clan-structured Rule in 13th Century Mongolia - Veronika Veit (Acta Mongolica, 2006)
The structure of Mongol society in the 12th and 13th century. according to the sources available to us. was based on the clan-system. The Mongolian clan formed a strictly agnatic or patrilineal unit. marriage alliances were guided by the principle of exogamy. Rashid ad-Din, the Persian scholar and long-term first minister of the Mongolian 11- khanate in genealogy, the since 13th century, informs us: all dispose of a carefully established Mongolian custom “demands it that they preserve the origin of their ancestors. To each child is told and explained his descent. There is, therefore, none among them who has not any knowledge of his tribe and his origins’. The knowledge of a регвоп 5 descent, however, was not only a question of family interest and social order, it was, moreover, a factor of considerable political relevance. To what extent this basically charcteristic feature of steppe-nomadic society contributed to the successful building of the Mongol Empire, and why it ultimately, not to say, inevitably, led to the empire’s decline and fall, is the topic of the paper in hand. [ will try to explain the process in three steps as given below.